The competitive effects of linking electricity markets across space and time - Thomas Tangerås; Frank A. Wolak (Research Institute of Industrial Economics (IFN), 2017)
We show that a common regulatory mandate in electricity markets that use location-based pricing that requires all customers to purchase their wholesale electricity at the same quantity-weighted average of the locational prices can increase the performance of imperfectly competitive wholesale electricity markets. Linking locational markets strengthens the incentive for vertically integrated firms to participate in the retail market, which increases competition in the short-term wholesale market. In contrast, linking locational markets through a long-term contract that clears against the quantity-weighted average of short-term wholesale prices does not impact average wholesale market performance. These results imply that a policy designed to address equity considerations can also enhance efficiency in wholesale electricity markets.
Keywords: C72; D43; G10; G13; L13; 330; Electricity markets; Equity; Market design; Market performance; Market power; Vertical integration